2020
DOI: 10.1186/s12911-020-01271-2
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning methods to predict in-hospital mortality of sepsis patients in the ICU

Abstract: Background Early and accurate identification of sepsis patients with high risk of in-hospital death can help physicians in intensive care units (ICUs) make optimal clinical decisions. This study aimed to develop machine learning-based tools to predict the risk of hospital death of patients with sepsis in ICUs. Methods The source database used for model development and validation is the medical information mart for intensive care (MIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…As mentioned above, sepsis prediction on the ICU is an important and timely problem and an active area of research. Under these circumstances, it is not surprising that some approaches have been developed in parallel to this work [33][34][35][36][37][38][39][40][41][42][43]. It will be an exciting and important avenue for future work to benchmark all these approaches (including ours) against each other and to compare their performances on a unified and realistic set of sepsis labels, for instance, the ones we propose in this work.…”
Section: Parallel Work On Sepsis Predictionmentioning
confidence: 97%
“…As mentioned above, sepsis prediction on the ICU is an important and timely problem and an active area of research. Under these circumstances, it is not surprising that some approaches have been developed in parallel to this work [33][34][35][36][37][38][39][40][41][42][43]. It will be an exciting and important avenue for future work to benchmark all these approaches (including ours) against each other and to compare their performances on a unified and realistic set of sepsis labels, for instance, the ones we propose in this work.…”
Section: Parallel Work On Sepsis Predictionmentioning
confidence: 97%
“…First, our results showed that MIMIC-III specific machine learning models using only 10 clinical variables outperformed nine commonly used severity scoring methods. Several related studies (e.g., [35-37]) have also shown that machine learning models outperform severity scores on predicting in-hospital mortality. Second, developing health system specific (or local) prediction models enables continuous improvements of the model by including more training data (as more data become available), adding new clinical or laboratory variables to the model, or re-training the model using newly developed machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…First, our results showed that MIMIC-III specific machine learning models using only 10 clinical variables outperformed nine commonly used severity scoring methods. Several related studies (e.g., [35][36][37]) have also shown that machine learning models outperform severity scores on predicting in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The threat of hospital mortality was higher in the latter group (18.7%) compared to the former group (8.4%). The use of the least absolute shrinkage and selection operator (LASSO), random forest (RF), gradient boosting machine (GBM), and the traditional logistic regression (LR) algorithms has been proposed by Kong et al (2020) [45], to predict the risk of in-hospital death for sepsis patients. Data were collected from MIMIC III as an ICU database including the diagnostic codes, vital signs, laboratory tests, demographics, and some other clinical characteristics of each patient between 18 and 90 years old.…”
Section: Literature Reviewmentioning
confidence: 99%